2015
DOI: 10.1158/1940-6207.capr-14-0386
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Is a Novel Target of Cancer Chemopreventative Isothiocyanates in Prostate Cancer Cells

Abstract: Isothiocyanates (ITCs) derived from cruciferous vegetables, including phenethyl isothiocyanate (PEITC) and sulforaphane (SFN), exhibit in vivo activity against prostate cancer in xenograft and transgenic mouse model, and thus are appealing for chemoprevention of this disease. Watercress constituent PEITC and SFN-rich broccoli sprout extract are under clinical investigations but the molecular mechanisms underlying their cancer chemopreventive effects are not fully understood. The present study demonstrates that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
(80 reference statements)
2
14
0
Order By: Relevance
“…Here, by using both in vivo and in vitro models, we show that the SVF of ppWAT is a rich source of growth factors, cytokines and chemokines that are produced at high levels in obese mice. The role of CXCL12-CXCR4 axis in progression of various cancers including PCa is well documented [2831]. However, the cell source of CXCL12 has remained unclear and whether this chemokine gradient contributes to caner-promoting effects of obesity has remained a subject of debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, by using both in vivo and in vitro models, we show that the SVF of ppWAT is a rich source of growth factors, cytokines and chemokines that are produced at high levels in obese mice. The role of CXCL12-CXCR4 axis in progression of various cancers including PCa is well documented [2831]. However, the cell source of CXCL12 has remained unclear and whether this chemokine gradient contributes to caner-promoting effects of obesity has remained a subject of debate.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 has been shown to be a key receptor in mediating the metastasis of multiple types of tumors [27]. The role of CXCL12-CXCR4 axis in cancer cell migration, invasion and metastasis has been demonstrated [2831]. AMD3100, a CXCR4 inhibitor, sensitizes PCa to chemotherapy [32], however the main source of CXCL12 and its contribution to obesity-associated cancer progression has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary and experimental studies demonstrated evidences that CXCL12/CXCR4 signaling pathway may be involved in metastatic prostate cancer progression . Prostate cancer cells isolated from bone metastasis had overexpression of CXCR4 and CXCR7 chemokine receptors .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary and experimental studies demonstrated evidences that CXCL12/CXCR4 signaling pathway may be involved in metastatic prostate cancer progression . Prostate cancer cells isolated from bone metastasis had overexpression of CXCR4 and CXCR7 chemokine receptors . Analysis of CXCR4 expression in humans using high‐density microarrays from a cohort of 600 patients demonstrated elevated levels of this chemokine receptor in metastatic prostate cancer .…”
Section: Discussionmentioning
confidence: 99%
“…SFN has been shown to inhibit the initiation of cancer by blocking damage caused by carcinogens through the induction of phase 2 enzymes via kelch-like ECH associated protein 1 (Keap1) and nuclear factor (erythroid-derived 2)-like 2 (Nrf2) signaling ( 10–13 ). In the transgenic adenocarcinoma of the mouse prostate (TRAMP) model of prostate cancer, broccoli consumption and/or SFN treatment has been shown to slow prostate cancer growth and metastasis ( 8 , 9 , 14 , 15 ). Several potential mechanisms have been implicated, including the induction of Nrf2-related pathways, inhibition of the cancer-promoting Akt signaling cascade, suppression of a chemokine receptor (CXCR4), and through augmenting the lytic activity of natural killer cells ( 8 , 9 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%